Analysis on Temporal and Spatial Characteristics of Vegetable Production in Guangdong Province from 1992 to 2020 - Shanshan FENG; Xu LIU; Junfen LIANG; Canfang ZHOU (Guangdong nongye kexue, 2023)
【Objective】The study aims to reveal the spatial and temporal changes of vegetable production in Guangdong Province from 1992 to 2020, with a view to providing a decision basis for the spatial distribution optimization and scientific development strategy of vegetable production in Guangdong Province.【Method】Based on the data of vegetable production in Guangdong Province from 1992 to 2020, the methods of time-series statistics, production scale index, production concentration index, and change monitoring were used to analyze the time-series changes, spatial differences, spatial and temporal distribution and change patterns of vegetable production in Guangdong Province from provincial, municipal and county scales, respectively.【Result】From the provincial scale, from 1992 to 2020, the vegetable sowing area, yield and unit yield in Guangdong Province had been in a fluctuating ascending trend, with the vegetable sowing area increased by 73.23×104 hm2 and vegetable yield increased by 2503.31×104 t. The vegetable unit yield in Guangdong Province increased from 19.07 t/hm2 in 1992 to 27.19 t/hm2 in 2020. From the municipal scale, the regions with larger vegetable sowing area and higher vegetable yield were mainly distributed in Guangzhou, Zhanjiang and Maoming; meanwhile, the regions with higher vegetable unit yield were mainly distributed in Shantou, Jieyang and Chaozhou. From the county scale, counties with vegetable sowing area of more than 2×104 hm2 or yield of more than 50×104 t showed as a significant upward trend, and the distribution pattern of these counties developed from scattered to aggregated contiguous. Further more, counties with vegetable unit yield of more than 30 t/hm2 were dominated by an upward trend, and the distribution pattern of these counties developed from a sporadic distribution in the eastern Guangdong area to a cluster of contiguous development in many regions of the whole province.【Conclusion】The results show that the vegetable production in Guangdong Province showed significant spatial and temporal divergence from 1992 to 2020. Therefore, vegetable production in Guangdong Province should be given full attention to regional advantages, and promote the efficiency, high-quality and specialization of vegetable production in various cities and counties on the basis of ensuring the stable production and supply of vegetables.